2007
DOI: 10.1086/513440
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Polymerase Chain Reaction Restriction Fragment–Length Polymorphism Genotyping ofTrypanosoma cruzi(Chagas Disease): Taxonomic and Clinical Applications

Abstract: MLP analysis represents a new alternative to existing molecular methods for T. cruzi typing. It might offer an invaluable support to clinical and epidemiological studies and to control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…They have been corroborated by many genetic markers, present some ecological and epidemiological specificities and exhibit differential protein expression patterns (Machin et al, 2014;Telleria et al, 2010). Interestingly, the six near-clades can be also discriminated by antigen genes (Rozas et al, 2007), although these genes undergo a strong selective pressure. This observation illustrates the strength of PCE in T. cruzi, which is reflected in all genes of this parasite, including strongly selected ones.…”
Section: Parasitic Protozoamentioning
confidence: 87%
See 1 more Smart Citation
“…They have been corroborated by many genetic markers, present some ecological and epidemiological specificities and exhibit differential protein expression patterns (Machin et al, 2014;Telleria et al, 2010). Interestingly, the six near-clades can be also discriminated by antigen genes (Rozas et al, 2007), although these genes undergo a strong selective pressure. This observation illustrates the strength of PCE in T. cruzi, which is reflected in all genes of this parasite, including strongly selected ones.…”
Section: Parasitic Protozoamentioning
confidence: 87%
“…Population genetic interpretation of MLEE variability made it possible to show that the 'zymodemes' (MLEE MLGs) evidenced by Miles' pioneering studies (1978) could be equated to genetic clones (Tibayrenc et al, 1981(Tibayrenc et al, , 1986. In this species, there is LD: (1) among MLEE loci (Tibayrenc et al, 1981(Tibayrenc et al, , 1986 and (2) between different kinds of markers: nuclear and mitochondrial polymorphisms (de Freitas et al, 2006;Machado and Ayala, 2001;Ramírez et al, 2011;Spotorno et al, 2008), random amplified polymorphic DNA (RAPD) and MLEE (Tibayrenc et al, 1993;Brisse et al, 2000), microsatellite polymorphism and DNA content , neutral markers and strongly selected antigen genes (Lima et al, 2012;Rozas et al, 2007), as well as neutral genetic markers and the protein polymorphism revealed by proteomic analysis (Telleria et al, 2010). Although Minning et al (2011) considered that their data suggested 'genetic exchange playing a major role in T. cruzi population structure', in their study, there is an obvious LD between CNV polymorphism and near-clade classification: all near-clade TCI strains clearly group together, as do all non-TCI strains (see their Fig.…”
Section: Parasitic Protozoamentioning
confidence: 99%
“…A T. cruzi marinkellei strain was used as outgroup. The complete description of each stock used in the study has been described elsewhere (Rozas et al 2007). …”
Section: Strainsmentioning
confidence: 99%
“…16 Using PCR-RFLP, Rozas and others reported TcI, TcIIb (currently TcII), TcIIa or TcIIc (currently TcIII and TcIV), and TcIId or TcIIe (TcV and TcVI) in single and mixed infections of mammals, Mepraia spinolai and humans from the Coquimbo Region, the hyperendemic area of Chile. 17 More recently, the presence of TcIII was documented in Triatoma infestans from Chile by using three microsatellite markers, with TcI, a hybrid (TcV + TcVI), and unknown lineages. 18 Chagas disease is endemic to Chile.…”
mentioning
confidence: 99%